The Magnitude of Binocular Disparity Modulates Search Time for Targets Defined by a Conjunction of Depth and Colour. - De La Rosa, Stephan; Moraglia, Giampaolo; Schneider, Bruce A. (Canadian Journal of Experimental Psychology, 2008)
Nakayama and Silverman (1986) proposed that, when searching for a target defined by a conjunction of color and stereoscopic depth, observers partition 3D space into separate depth planes and then rapidly search each such plane in turn, thereby turning a conjunctive search into a “feature” search, in their study, they found, consistent with their hypothesis, shallow search slopes when searching depth planes separated by large binocular disparities. Here, the authors investigated whether the search slope depends upon the extent of the stereoscopic ally induced separation between the planes to be searched (i.e., upon the magnitude of the binocular disparity. The obtained slope shows that (1) a rapid search only occurs with disparities greater than 6 min of arc, a value that vastly exceeds the stereo threshold, and that (2) the steepness of this slope increases in a major way at lower disparities. The ability to implement the search mode envisaged by Nakayama and Silverman is thus clearly limited to large disparities; less efficient search strategies are mandated by lower disparity values, as under such conditions items from one depth plane may be more likely to “intrude” upon the other. Reprinted by permission of the publisher.